A target environment programming language to improve developer's productivity: a case study - Metrôlho, J.C.M.M. (2010)
This paper presents a target-specific programming language (TSL) that was designed to improve the design cycle of code generation for an industrial embedded system. The native assembly code, the new language structure and their constructs, are presented in the paper. The proposed TSL is expressed using words and terms that are related to the target’s domain and consequently it is now easier to program, understand and to validate the desired code. It is also demonstrated the language efficiency by comparing some code described using the new language against the previous used code. The design cycle is improved with the usage of the TSL because description time and debug time are significantly reduced with this new software tool. This is also a case of university-industry partnership.